Modulation of the CO2 fixation in dinickel azacryptands. Issue 17 (21st February 2017) - Möller, F.; Castañeda-Losada, L.; Junqueira, J. R. C.; Miller, R. G.; Reback, M. L.; Mallick, B.; van Gastel, M.; Apfel, U.-P.
Abstract : Different linker molecules within the dinickel azacryptand moiety show strong influence towards their CO2 coordination behaviour. Abstract : While bimetallic azacryptands are known to selectively coordinate CO2, there is little knowledge on how different substitution patterns of the azacryptand cage structure influence CO2 coordination. Stopped-flow UV-vis spectroscopy, electrochemical analysis and DFT calculations were performed on a series of dinickel azacryptands and showed different rates of CO2 coordination to the complexes. We herein present data showing that the different flexibility of the azacryptands is directly responsible for the difference in the CO2 uptake capability of dinickel azacryptand complexes.